Predicted demand for 3 kg LPG gas in each provinces area in Indonesia - Novaria, Rachmawati; Alfiah, Agry; Khaddafi, Muammar; Tukino, Tukino; Sudipa, I Gede Iwan (Jurnal Info Sains : Informatika dan Sains, 2024)
Predicted the demand for 3 kilograms of LPG gas in different provinces of Indonesia is crucial for assuring the provision of energy to households. By employing the Exponential Triple Smoothing (ETS) technique, this study examines demand-influencing factors and consumption patterns. By integrating historical data's levels, trends, and seasonality, ETS enables accurate and timely forecasts. The findings illustrate the predicted outcomes for the ten provinces in Indonesia that have the highest demand for 3 kilograms of LPG gas, as well as the ten provinces that have the lowest demand across all regions. All provinces' MAPE forecasting error testing results utilizing the ETS method are incorporated with an exceptionally high degree of precision, given that the error rate is 5.27%.